Identification of Prognostic Biomarkers for Multiple Solid Tumors Using a Human Villi Development Model - Zhang, Botao; Wang, Yuanjing; Li, Hongxia; Feng, Lin; Li, Wenbin; Cheng, Shujun (Frontiers in Cell and Developmental Biology, 2020)
The processes of embryonic development that rely on epithelial-mesenchymal transition (EMT) for the implantation of trophoblast cells are co-opted by tumors, reflecting their inherent uncontrolled characteristics and leading to invasion and metastasis. Although tumorigenesis and embryogenesis have similar EMT characteristics, trophoblasts have been shown to exhibit "physiological metastasis" or be "pseudo-malignant", resulting in different outcomes. The gene co-expression network is the basis of embryonic development and tumorigenesis. We hypothesize that if the gene co-expression network in tumors is “off-track” from that in villi, it is more likely to develop into malignant tumors and have a worse prognosis, and we proposed the “off-track theory” for the first time. In this study, we examined gene co-expression networks in villi and multiple solid tumors. Through network functional enrichment analyses, we found that most tumors and villi exhibited a significantly enriched EMT, but the genes that performed this function were not identical. Then, we identified the “off-track genes” in the EMT-related gene interaction network using the “off-track theory”, and through survival analysis, we discovered that the risk score of “off-track genes” was associated with poor survival of cancer patients. Our study indicated that villi development is a reliable and strictly regulated model that can illuminate the trajectory of human cancer development and that the gene co-expression networks in tumor development are “off-track” from those in villi. These “off-track genes” may have a substantial impact on tumor development and could reveal novel prognostic biomarkers.